Morphological Characterization of Bread Wheat (Triticum aestivum L.) Genotypes Grown in the Sudan Savanna of Nigeria - Mustafa, Abubakar Alhaji; Mohammad, Saquib; Aminu, Dattijo (Nepal Journal of Botany, 2025)
Bread wheat is a self-pollinating, annual, and temperate crop. It is a crop with various uses both for man and his animals. Depending on culture and region, wheat is utilized for bread baking, chappati, biscuits, pasta, macaroni, noodles alkaki, pinkaso, dubula, chin chin, gurasa, local spaghetti (taliya), meat pie and many more products. Information on genetic diversity is important for crop improvement. A study was conducted during the cold harmattan season (November to March) at Maiduguri under irrigated condition during November, 2018 to March, 2019. The objective was to characterize some important qualitative characters in wheat, using standard wheat hand book descriptors (dense, very dense and intermediate); awnedness (short, conspicous); seed size (medium, large); degree of seed shrivelness (plump, intermediate); leaf sheath colour (white, chalky white); leaf size (broad, narrow); grain type (bold, medium); glume colour (white, whitish brown); seed colour (red, white); awn length (long, moderate). The observations suggest that these genotypes can be utilized for crop improvement in future breeding programmes.